Evaluation of the Effect of Two Systemic Doses of HESA-A on Prevention of Induced Tongue Neoplasm in Rats - Masoumeh Mehdipour; Ali Taghavi Zenouz; Mehran Mesgari Abbasi; Daryoush Mohajeri; Hossein Damghani; Sanaz Helli; Bita Abdollahi (Tabriz University of Medical Sciences, 2013)
Background and aims. The aim of the present study was to compare the inhibitory effects of two systemic doses of HESA-A on prevention of 4-NQO-induced tongue neoplasms in rats. This study evaluated weight and histopathological changes. Materials and methods. Forty-eight male Sprague Dawley rats were divided into four groups of A, B, C and D of each 12 rats. The rats in groups B to D received 30 ppm of 4-Nitroquinoline-1-oxide (4-NQO) in drinking water for 12 weeks. When feeding with 4-NQO was initiated, the rats in groups B and C received HESA-A at doses of 250 and 500 mg/kg, respectively, 3 times a week. Body weights were measured three times a week. At the end, the rats were euthanized and the tongue was removed. Histological evaluations for carcinogenesis were carried out under a light microscope. Results. The mean body weights of rats in groups B, C and D were significantly lower than that in group A (P < 0.05). There were no significant differences in weight changes between groups B, C and D. In the present study, after 12 weeks of treatment, Tongue specimens in groups B and C did not exhibit severe dysplastic changes; however, concurrent hyperplasia, without atypia and mild-to-moderate dysplastic changes were detected. These changes were significantly less than those in group D, with significant differences between group D and groups A, B and C (P<0.001, P<0.01 and P<0.05, respectively). Conclusion. HESA-A has dose-dependent inhibitory effects on the development of neoplasms of the tongue.